Answer:
x = -2, 3.
Step-by-step explanation:
x^2 - x - 6 = 0
(x - 3)(x + 2) = 0
x = -2. 3.
Answer:
2.7x10^7 or 2.70000000 I think
Step-by-step explanation:
The best way to solve is by using elimination method.
20x = -58 - 2y
17x = -49 - 2y
Multiply second equation by -1
20x = -58 - 2y
-17x = 49 + 2y
Add equations.
3x = -9
Divide.
x = -3
Plug in -3 into one of the equations.
17(-3) = -49 - 2y
-51 = -49 - 2y
Add 49 to both sides.
-2 = -2y
Divide.
1 = y
So your solution is (-3, 1).
I hope this helps love! :)
Answer:
A. 2 acute and 1 right angle.